If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 4 = (4x + -3) Reorder the terms: 4 + 8x = (4x + -3) Reorder the terms: 4 + 8x = (-3 + 4x) Remove parenthesis around (-3 + 4x) 4 + 8x = -3 + 4x Solving 4 + 8x = -3 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 4 + 8x + -4x = -3 + 4x + -4x Combine like terms: 8x + -4x = 4x 4 + 4x = -3 + 4x + -4x Combine like terms: 4x + -4x = 0 4 + 4x = -3 + 0 4 + 4x = -3 Add '-4' to each side of the equation. 4 + -4 + 4x = -3 + -4 Combine like terms: 4 + -4 = 0 0 + 4x = -3 + -4 4x = -3 + -4 Combine like terms: -3 + -4 = -7 4x = -7 Divide each side by '4'. x = -1.75 Simplifying x = -1.75
| 5k+6k=11 | | 10-v-17v=4 | | 3(y+2)=16(2y) | | -7h-4h-3= | | 5y^2-2=-3y | | 2-f=(f/5) | | g(x)=3x-2 | | 2-2n-4n=8 | | 5xn-18-4xn=-36 | | 3(y+2)=6(2y) | | (x/5)-12=7 | | -7x-3(-3x-20)=46 | | -8(5n+9)=11n | | 5xn-18-4xn=36 | | 2.5x+1.5=-9.5 | | 9=19x+39-4x | | 4(t-5)-3=6t-13 | | 12-3(5x-7)-4x=71 | | 0.75x+0.2x=x-2 | | 25-x=7 | | (wx)2= | | 3(8-3(1))=5(2+1) | | 7z=180-22 | | (8-3(1))=5(2+1) | | 27x^3-1= | | 9x^2-28x+3=0 | | -3p+7=6-10p-5 | | 9x+7=3x-9 | | 2r-6r=12 | | -(c-12c-c-3c)= | | 4(b+3)=24 | | -18-6k=6(p-8) |